(untitled) (UNED Research Journal, 2019)
Introduction: The genus Myroxylon (Fabaceae) includes two Neotropical species, M. balsamum and M. peruiferum, both present from southern Mexico to South America. Despite this wide distribution, only the presence of M. balsamum was recognized in Costa Rica. Objectives: to confirm the presence of M. peruiferum in Costa Rica and to present the morphological characteristics for its differentiation from M. balsamum. Methods: In April 2019, three sites southwest of the Central Valley were explored. Botanical material was collected from trees of the Myroxylon genus and identified at the species level. Additionally, the collections of herbaria CR, JVR and USJ were reviewed. Results: M. peruiferum trees were found in the three explored sites, differentiable from M. balsamum in the morphology of the leaflets, flowers, mature fruits and seeds. 41% of the herbarium specimens identified as M. balsamum actually correspond to M. peruiferum. Conclusion: the absence of M. peruiferum in the records of the Costa Rican flora was due to the incorrect identification of the collected material and the ignorance that the species can be identified by vegetative characters.